Non-linear rheological (LAOS) behavior of sourdough-based dough - Yildirim-Mavis, Cigdem; Yilmaz, Mustafa Tahsin; Dertli, Enes; Arici, Muhammet; Ozmen, Duygu (ELSEVIER SCI LTD, 2019)
During processing, wheat dough is known to undergo large deformation led by mixing and fermentation processes. This deformation is much more pronounced when sourdough is used in the recipe of wheat dough whose gluten is considerably hydrolyzed during sourdough fermentation. This causes deeper effects on rheological properties and shelf life of bakery products. Traditional small amplitude oscillatory tests do not enable us to comprehend the viscoelasticity under large deformations. In this respect, large amplitude oscillatory shear ( LAOS) tests are useful for accurate characterization of the non-linear mechanical response. This study, therefore, is undertaken to investigate the non-linear mechanical response of dough prepared with different amounts of sourdough (0, 10, 20 30 and 40%) in a strain values ranging from 0.005 to 200% (frequency at 10 rad/s). As a result, sourdough was determined to have considerable effects on the non-linear viscoelastic response of dough. Strain-stiffening and shear-thinning behaviors were considerably influenced by sourdough incorporation and the dough started to show strain-softening and lowered shear-thinning behavior after giving a peak around at 100% strain due to the onset of the breakdown of the gluten network and suspension of starch matrix as consequence of the metabolic activity of the starter culture (Lactobacillus brevis E25) used in the preparation of sourdough. The physicochemical (pH and TTA), microbiological properties (LAB count) and extensographic properties were also shown to support the LAOS results. LAOS tests could be effectively and clearly used to reveal the effect of processing conditions (sourdough content and deformation by large strain amplitude) on the non-linear mechanical response of wheat dough.
Keywords: Sourdough; LAOS parameters; Non-linear rheology; Lissajous-bowditch curves; AMPLITUDE OSCILLATORY SHEAR; LACTIC-ACID BACTERIA; ORAL PROCESSING BEHAVIOR; WHEAT SOURDOUGH; LACTOBACILLUS-BREVIS; SHELF-LIFE; BREAD; FERMENTATION; GLUTEN; OPTIMIZATION; Chemistry; Food Science & Technology